Similkameen-Okanogan Region - COPP, Stanley A (2005)
The Okanogan and Similkameen Valleys of north-central Washington and south-central British Columbia share many attributes over 8-10,000 years, beginning with Windust and/or Cascade Phase cultures. Stronger cultural ties are associated with Columbia Plateau sequences, but influences from the outhern Fraser Plateau are significant at times. This paper examines inter and intra-valley and extra-areal similarities and differences in projectile point types, and sheds light on larger issues such as Columbia-Fraser Plateau interaction spheres.